2012
DOI: 10.1111/j.1751-7893.2012.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Process of implementation and development of early psychosis clinical services in Italy: a survey

Abstract: Our data are consistent with worldwide literature showing a slow and variable implementation of early psychosis services in all nations. The main efforts to make these services diffused should be addressed to favour the process of localized adaptation to the guidelines, to demand possible and realistic implementation of the standard method, to stimulate policy endorsement and resources' allocation, and to particularly support the rural and the poorer zones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
54
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(55 citation statements)
references
References 12 publications
1
54
0
Order By: Relevance
“…Despite this, only a small part of respondents (about a third) reported that EI protocols were operational in the context of their services, in most cases for patients with psychotic disorders. This is consistent with previous studies indicating a slow diffusion of early interventions in Italy (Cocchi et al, 2011a;Ghio et al, 2012).…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…Despite this, only a small part of respondents (about a third) reported that EI protocols were operational in the context of their services, in most cases for patients with psychotic disorders. This is consistent with previous studies indicating a slow diffusion of early interventions in Italy (Cocchi et al, 2011a;Ghio et al, 2012).…”
Section: Discussionsupporting
confidence: 94%
“…This problem seems to be present on a worldwide scale, as even in Australia, which was one of the first countries to start a reform towards EI, implementation has been affected by insufficient allocation of resources to appropriately support the reform focus (Catts et al, 2010). In this regard, it should be also noted that the Italian EI services are being mostly developed according to a "specialist within generalist team" model (Cocchi et al, 2011a;Ghio et al, 2012), mainly due to lack of funding and in contrast with other experiences that favor the implementation of specific and independent outpatient services (Edwards et al, 2002).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Research findings support a number of key elements of early intervention programs, yet there is variability in their implementation (Catts et al, 2010;Ghio et al, 2012;McGorry et al, 2008;Srihari et al, 2012). Some programs stress the importance of case management, while others focus on medication or social and functional recovery (Garety et al, 2006;Spencer et al, 2001).…”
Section: Introductionmentioning
confidence: 77%